2020
DOI: 10.1136/ijgc-2019-001032
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity lymphedema in patients with gynecologic malignancies

Abstract: Lower extremity lymphedema is a chronic, often irreversible condition that affects many patients treated for gynecologic malignancies, with published rates as high as 70% in select populations. It has consistently been shown to affect multiple quality of life metrics. This review focuses on the pathophysiology, incidence, trends, and risk factors associated with lower extremity lymphedema secondary to the treatment of cervical, endometrial, ovarian, and vulvar cancers in the era of sentinel lymph node mapping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 65 publications
0
68
2
1
Order By: Relevance
“…Patients that undergo simple/radical hysterectomy or radical trachelectomy may experience surgical complications such as bladder dysfunction, vascular or ureteral injuries, and blood loss among others 16 . In addition, 10% to 41% of patients treated with LN dissection can experience lower extremity lymphedema as postoperative morbidity 17 , 18 . Importantly, the literature indicates that few patients with early FIGO stage tumors have evidence of LN metastasis, seen in <1% of patients with stage IA1 tumors and in ~2% of patients with stage IA2 tumors 19 .…”
Section: The Silva Pattern-based Classification For Hpv-associated Admentioning
confidence: 99%
“…Patients that undergo simple/radical hysterectomy or radical trachelectomy may experience surgical complications such as bladder dysfunction, vascular or ureteral injuries, and blood loss among others 16 . In addition, 10% to 41% of patients treated with LN dissection can experience lower extremity lymphedema as postoperative morbidity 17 , 18 . Importantly, the literature indicates that few patients with early FIGO stage tumors have evidence of LN metastasis, seen in <1% of patients with stage IA1 tumors and in ~2% of patients with stage IA2 tumors 19 .…”
Section: The Silva Pattern-based Classification For Hpv-associated Admentioning
confidence: 99%
“…Pelvic lymphadenectomy is part of primary surgical treatment of all stages of cervical carcinoma except stage IA1 without lymphovascular invasion 9 . Sentinel lymph node (SLN) mapping and biopsy of pelvic lymph nodes for early stage cervical cancer has emerged as a strategy to mitigate the risk for lower extremity lymphadenoma that accompanies systematic pelvic lymphadenectomy 26 . SLN mapping also helps identify unusual lymph drainage patterns 54 .…”
Section: Lymph Node Specimensmentioning
confidence: 99%
“…Lower extremity lymphedema, characterized by accumulation of interstitial fluid, soft tissue swelling, and chronic inflammation, remains a common complication after lymphadenectomy performed in the setting of gynecologic cancer. 1 While the overall incidence of lower extremity lymphedema is approximately 25%, rates vary depending on which lymph node basin is interrupted and the number of lymph nodes removed. Inguinofemoral lymph node dissection, performed in conjunction with vulvar cancer surgery, is associated with the highest rate of lower extremity lymphedema, with rates approaching 75% in studies assessing patient reported symptoms.…”
Section: Gynecological Cancermentioning
confidence: 99%
“…These include lymphatic-lymphatic bypass (anastomosis of lymphatics), lymphovenous bypass (anastomosis of afferent lymphatics to the venous circulation), and vascularized lymph node transfer among others. 1 Immediate lymphatic reconstruction aims to prevent lymphedema from developing, and involves lymphovenous bypass at the time of lymphadenectomy. A 2018 systematic review of 12 studies across tumor types and inclusive of axillary and groin lymphadenectomies showed a relative risk of 0.33 of developing lymphedema in patients undergoing immediate lymphatic reconstruction.…”
Section: Gynecological Cancermentioning
confidence: 99%